2014
DOI: 10.1111/gove.12067
|View full text |Cite
|
Sign up to set email alerts
|

Governance Delegation Agreements: Shared Sovereignty as a Substitute for Limited Statehood

Abstract: Governance delegation agreements—international treaties allowing external actors legal authority within host states for fixed terms—succeed in simple and, under certain conditions, complex state‐building tasks. These deals are well institutionalized and have input legitimacy because ratification requires sufficient domestic support from a ruling coalition. In order to obtain that input legitimacy, however, host states constrain external actors commensurate with their level of statehood: Stronger states delegat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…Her statistical analysis of United Nations Chapter VI Peacekeeping Missions that are based on the consent of the host country and, thus, represent delegation agreements, demonstrates the ability of these missions to significantly reduce the levels of violence. Her statistical findings, based on Chapter VI interventions alone, are more positive than those of Lake and Fariss, whose database includes Chapter VII, which do not require country consent, as well as Chapter VI interventions (compare Lake and Farris and Matanock 2014). Unlike trusteeships, delegations agreements, although complex, have a good chance of securing input legitimacy because they are the result of contracting.…”
Section: The Dependent Variables: State Capacity and The Provision Ofmentioning
confidence: 92%
See 3 more Smart Citations
“…Her statistical analysis of United Nations Chapter VI Peacekeeping Missions that are based on the consent of the host country and, thus, represent delegation agreements, demonstrates the ability of these missions to significantly reduce the levels of violence. Her statistical findings, based on Chapter VI interventions alone, are more positive than those of Lake and Fariss, whose database includes Chapter VII, which do not require country consent, as well as Chapter VI interventions (compare Lake and Farris and Matanock 2014). Unlike trusteeships, delegations agreements, although complex, have a good chance of securing input legitimacy because they are the result of contracting.…”
Section: The Dependent Variables: State Capacity and The Provision Ofmentioning
confidence: 92%
“…Second, state‐building efforts that proceed from contracting (by delegation, see Matanock 2014, or by interstate agreements, see Börzel and van Hüllen 2014) are more likely to be successful. At a minimum, contracting makes input legitimacy much more likely because the political elites governing the country must positively agree to terms.…”
Section: The Dependent Variables: State Capacity and The Provision Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Aila Matanock has recently shown that there are "delegation agreements" between countries that have produced desirable outcomes. 48 For example, confronted with growing violence and rising corruption the Governor General of the Solomon Islands requested Australia to take over law enforcement in 2003. The Australian-led Regional Assistance Mission to the Solomon Islands (RAMSI) "brought in more than 2,000 soldiers and other personnel and succeeded in establishing the rule of law before departing in 2013.…”
Section: Defending Foreign Involvementmentioning
confidence: 99%